Model of multimodal transport node functioning - Naumov, Vitalii; Nagornyi, Ievhen; Litvinova, Yana (Archives of Transport, 2015)
To increase the efficiency of transport nodes functioning taking into account the logistics management principles it is necessary to optimize the structure and capacity of transport nodes' production resources, and to develop such a method for calculating of joint schedules for vehicles and freight hubs of the transport node, which takes into account stochastic nature of the parameters of material and informational flows. For solving the problems of optimal management of transport nodes functioning processes it is proposed to use the specific efficiency indicator, which is determined as a ratio of total costs of clients servicing in transport node to the costs of production resources used while servicing. According to the used approach for formalization of the transport node internal processes, development of the simulation model was implemented on the base of object-oriented programming principles. TransportNode.dll class library has been used as basic tool for simulations. The model implemented on the base of the library allows to take into account stochastic nature of demand and probabilistic nature of technological processes in transport nodes. Some results of numeric simulations for the loading area “Amur-Gavan” of Dnipropetrovsk River Port have been described in the paper.